Peer Editing to Enhance Student’s Critical Thinking In Recount Text - Pasaribu, Maria; Valentina, Viola; Talunohi, Yariani; Lumbanbatu, Alivian G; Husda, Azizah (Tadris Pendidikan Bahasa Inggris IAIN Langsa, 2023)
This research focuses on peer review as a pedagogical strategy that can help students improve their writing and critical thinking skills.If students are to succeed in the modern world, they must acquire critical thinking (CT) skills, which are essential skills. This study uses a qualitative approach. The data collected specifically consists of written learning activities that use literary works as teaching materials. The aims of the study is to understand how peer editing improves students' critical thinking through recount text. The results of this study indicate that peer editing techniques have an influence on students' critical thinking skills in writing recount texts. Students get good grades gradually in the final cycle, with the average student score in the initial test of 63.2, the average student score in the first cycle is 75.4, and the student average score in the second cycle is 80. 3. In conclusion, peer editing techniques can improve students' thinking skills in writing recount texts.